STUDI KRITIS ATAS TEORI TARJAMAH ALQUR’AN DALAM ‘ULUM ALQUR’AN - Fadhli Lukman (UIN Raden Mas Said Surakarta, 2016)
History of the Qur’an has showed numbers of its translations into various languages, including Indonesian Language. Even the existence and the roles of translations in society are evidently needed, but its theoretical discourse within the field of ‘Ulum Alqur’an is still ambiguous. This paper attempts to describe the theoretical debate in Qur’anic translation and examine it through the existed Qur’anic translation in Indonesia. The basic argument built is that the theory of tarjamah Alqur’an within ‘Ulum Alqur’an has several theoretical problems: first, the categorization of harfiyyah and tafsiriyyah are not clearly operative; second, the terminology of tarjamah is implied to be meaningless; and third, there is no clear-cut concept of tarjamah dan tafsir. This problem rose from the stringency in the meaning of tarjamah and theological burden to emphasize i’jiz of the Qur’an. Hereby, widening the meaning of tarjamah as an alternative solution is needed.